Answer:
D. 4r + 3(10 – r) = 37
Explanation:
Let r be the roller coaster ride. Since it costs 4 tickets, this gives us the expression 4r.
We know that there were 10 rides total; this leaves Michael 10-r for the number of times he rode the boat ride.
Each boat ride costs 3 tickets; this gives us the expression
3(10-r)
Together, this gives us
4r+3(10-r) = 37
Answer:
A ride on the roller coaster costs 4 tickets while the boat ride only costs 3 tickets. Michael went on the two rides a total of 10 times and spent a total of 37 tickets.
A table titled Ride Tickets, showing Times on the Ride, Tickets per Ride, and Total Tickets. The first row shows Roller Coaster, with r, 4 and 4 r. The second row shows Boat Ride, with 10 minus r, 3, and 3 left parenthesis 10 minus r right-parenthesis. The third row shows, Total, with 10, blank, and 37.
Which equation is true?
r(10 – r) = 10
r + (10 – r) = 4 + 3
4r[3(10 – r)] = 37 this is your answer
4r + 3(10 – r) = 37
Step-by-step explanation:
Hayley begins solving this problem by combining like terms. 3x + 5x = 10 Which problem begins the same way? A) 5x = 20 Eliminate B) 2(x + 5) = 20 C) x 4 = 30 D) 4x ? 2x = 10
Answer:
In a linear equation of one variable there are two terms terms containing variable and constant.
Variable means term containing x,y,z which act as variables. and constant means any rational number . In higher classes you can include real number also.
The given equation is 3x + 5x = 10
So, the solution out of four options is A) 5x = 20.
Here variable is on one side of equation and constant on other side.
But Option (D) looks absolutely correct if we replace ? by either + sign or Negative (-) sign.
Answer:
D. [tex]4x-2x=10[/tex]
Step-by-step explanation:
We have been give an equation [tex]3x+5x=10[/tex]. The equation is solved by combining like terms. We are asked to choose the equation that an be solved by combining the like terms.
Let us check our given choices one by one.
A. [tex]5x=20[/tex]
We can see that equation A will be solved by dividing 20 by 5, therefore, option A is not correct choice.
B. [tex]2(x+5)=20[/tex]
We can see that equation B will be solved by dividing 20 by 5 and then subtracting 5, therefore, option B is not correct choice.
C. [tex]\frac{x}{4}=20[/tex]
We can see that equation C will be solved by multiplying 20 by 4, therefore, option C is not correct choice.
D. [tex]4x-2x=10[/tex]
We can see that equation D will be solved by combining like terms, therefore, option D is correct choice.
The estimated insurance loss from a hurricane was $18.218.2 billion. This was $12.412.4 billion more than the loss from a tsunami three years later. What was the estimated insurance loss from the tsunami?
Answer:
If you are asking about the difference between the two, the difference is $5,805.80
Step-by-step explanation:
find dy/dx by implicit differentiation. 5+4x=sin(xy^2)
To find dy/dx by implicit differentiation, differentiate both sides of the equation with respect to x. The derivative of sin(xy^2) with respect to x is cos(xy^2) * (y^2 * dx/dx + x * d(y^2)/dx). Simplify the expression to find dy/dx.
Explanation:To find dy/dx by implicit differentiation, we will differentiate both sides of the equation with respect to x.
We have the equation 5+4x=sin(xy^2). Taking the derivative of both sides, the left side will be 0 since it is a constant. On the right side, we use the chain rule.
The derivative of sin(xy^2) with respect to x can be written as cos(xy^2) * (y^2 * dx/dx + x * d(y^2)/dx).
Simplifying further, dy/dx = (cos(xy^2) * (2xy^2 + x * 2y * dy/dx)) / (1 - x * 2y^2 * cos(xy^2)).
What are the values of m and n in the matrix addition below?
ANSWER
The correct answer is [tex]m=45,n=12[/tex].
EXPLANATION
We were given the matrix equation;
[tex]\left[\begin{array}{cc}n-1&6\\-19&m+3\end{array}\right] +\left[\begin{array}{cc}-1&0\\16&-8\end{array}\right] =\left[\begin{array}{cc}10&6\\-3&40\end{array}\right][/tex].
We must first simplify the Left Hand Side of the equation by adding corresponding entries.
[tex]\left[\begin{array}{cc}n-1+-1&6+0\\-19+16&m+3-8\end{array}\right]=\left[\begin{array}{cc}10&6\\-3&40\end{array}\right][/tex].
That is;
[tex]\left[\begin{array}{cc}n-2&6\\-3&m-5\end{array}\right]=\left[\begin{array}{cc}10&6\\-3&40\end{array}\right][/tex].
Since the two matrices are equal, their corresponding entries are also equal. we equate corresponding entries and solve for m and n.
This implies that;
[tex]n-2=10[/tex]
We got this equation from row one-column one entry of both matrices.
[tex]n=12[/tex]
Also, the row three-column three entries of both matrices will give us the equation;
[tex]m-5=40[/tex]
[tex]m=45[/tex]
Hence the correct answer is [tex]m=45,n=12[/tex].
The correct option is option 2
Sam initially invested $4,500 into a savings account that offers an interest rate of 3% each year. He wants to determine the number of years, t, for which the account will have less than or equal to $7,020.
Every year, Sam will have 103% of the amount from the previous year.
[tex]p\%=\dfrac{p}{100}\\\\103\%=\dfrac{103}{100}=1.03[/tex]
After the first year:
[tex]1.03\cdot\$4,500[/tex]
After the second year:
[tex]1.03\cdot1.03\cdot\$4,500=\$4,500(1.03)^2[/tex]
After the t-th year:
[tex]\$4,500(1.03)^t[/tex]
Therefore we have the inequality:
[tex]\$4,500(1.03)^t\leq\$7,020\ \ \ \ |\text{divide both sides by \$4,500}\\\\(1.03)^t\leq1.56\\\\(1.03)^{15}\approx15.56\\\\\text{therefore}\ t\leq15[/tex]
Answer: t ≤ 15.A party host is making identical party bags for guests using 44 bottles of bubbles, 89 stickers, and 55 pencils. What is the greatest number of identical party bags the host can make with the least amount of items leftover? Describe the contents of each bag.
Answer: 11 party bags with 1 sticker leftover
Each bag contains 4 bubbles, 8 stickers, and 5 pencils.
Step-by-step explanation:
Find the GCF of 44 (bubbles), 89 (stickers), and 55 (pencils)
44: 2 x 2 x 11
89: prime so choose 88 with 1 leftover
88: 2 x 2 x 2 x 11
55: 5 x 11
GCF = 11
Disregard the GCF to see how many of that item should go in each bag.
Bubbles: 2 x 2
Stickers: 2 x 2 x 2
Pencils: 5
Which correctly describes the point of discontinuity of the function?
A real-valued univariate function f=f(x) has a jump discontinuity at a point [tex]x_0[/tex] in its domain provided that
[tex]\lim \limits_{x\to x_0^-}f(x)=A_1[/tex]
and
[tex]\lim \limits_{x\to x_0^+}f(x)=A_2[/tex]
both exist and that [tex]A_1\neq A_2.[/tex]
As you can see at x=-3,
[tex]\lim \limits_{x\to -3^-}f(x)=6,[/tex] [tex]\lim \limits_{x\to -3^+}f(x)=9[/tex] and [tex]6\neq 9.[/tex]
Therefore, there is a jump discontinuity at x=-3.
Answer: correct choice is A.
What value of x makes the equation 3x-(7+4x)=2(5x-4)+1 true
x = 0
distribute parenthesis on both sides of the equation and simplify
3x - 7 - 4x = 10x - 8 + 1
- x - 7 = 10x - 7 ( subtract 10x from both sides )
- 11x - 7 = - 7 ( add 7 to both sides )
- 11x = 0 ( divide both sides by - 11 )
x = 0
Five cats each ate 1/4 cup of cat food. How much food did the five cats eat?
Answer: Five cats ate 1 and a quarter of cat food.
Step-by-step explanation
Given:-
Cat food ate by one cat = 1/4 cup
Cat food ate by five cats =[tex]5\times \frac{1}{4} \text{ [Multiplying both sides with 5 ]}\\\\=\frac{5}{4}=\frac{4+1}{4}=\frac{4}{4}+\frac{1}{4}=1+\frac{1}{4}[/tex]=1 and 1/4 cup.
Therefore cat food ate by five cats = 1 and a quarter of cup.[ here a quarter =1/4]
What is the justification for each step in the solution of the equation?
23x−13=2(x+2) Given
2x−1=6(x+2)
2x−1=6x+12 Distributive Property
2x=6x+13
−4x=13 Addition or Subtraction Property of Equality
x=−134
For this case we have the following equation:
[tex]\frac{2}{3}x-\frac{1}{3}= 2 (x + 2)\\[/tex]
If we multiply both sides of the equation by 3 we get:
[tex]2x-1 = 6 (x + 2)[/tex] ---> Multiplication Property of Equality
Applying the distributive property we have:
[tex]2x-1 = 6x + 12[/tex] ---> Distributive Property
Adding 1 on both sides of equality we have:
[tex]2x-1 + 1 = 6x + 12 + 1\\[/tex]
[tex]2x = 6x + 13[/tex] ---> Addition Property of Equality
Subtracting [tex]6x[/tex] on both sides we have:
[tex]-6x + 2x = 6x-6x + 13\\[/tex]
[tex]-4x = 13[/tex] ---> Subtraction Property of Equality
Finally, dividing by -4 on both sides we have:
[tex]\frac{-4x}{-4}= \frac{13}{-4}\\[/tex]
[tex]x = -\frac{13}{4}[/tex]---> Division Property of Equality
A survey was sent to GCA students asking the question "Who is your favorite teacher?" (Just FYI - Mrs. Parker received the most votes) What type of data was collected? Question 1 options: Quantitative Qualitative Continuous Discrete Question 2 (1 point) Question 2 Unsaved A survey was sent to GCA students asking the question "On a scale of 1 to 5, with 1 being the lowest and 5 being the highest, how would you rate your AMDM teacher?" The data collected was Question 2 options: Quantitative Qualitative Continuous redundant since every student rated their AMDM teacher as a 5. Question 3 (1 point) Question 3 Unsaved You decided to attend the GCA outing at Stone Mountain. Before you left for the park, you entered the park address into a GPS/Traffic app on your phone. The app told you that Stone Mountain was 47.6 miles from your house. 47.6 miles is an example of... Question 3 options: Qualitative, continuous data Quantitative, discrete data Qualitative, discrete data Quantitative, continuous data Question 4 (1 point) Question 4 Unsaved While you were at the Stone Mountain outing, you played a game of corn hole. You counted the number times you tossed the beanbag into the hole. The number of times you were able to sink the beanbag is an example of.... Question 4 options: Qualitative, continuous data Quantitative, discrete data Qualitative, discrete data Quantitative, continuous data Question 5 (1 point) Question 5 Unsaved You recorded the time you left Stone Mountain and the time you arrived home. You calculated time it took you get home was 57.28 minutes. 57.28 minutes is an example of.... Question 5 options: Qualitative, continuous data Quantitative, discrete data Qualitative, discrete data Quantitative, continuous data
1. Qualitative
2. Quantitative
3. Quantitative, continuous data
4. Quantitative, discrete data
5. Quantitative, continuous data
joshua can wash 5 cars in 1 hour and jason can wash 3 cars in one hour. at this rate, how long will it yake joshua and jason to wash 26 cars if they work together?
The answer is 3 hours 40 minutes
Given the graph of a line y=−x. Write an equation of a line which is perpendicular and goes through the point (8,2).
When a line is perpendicular to another line, the slope is the negative reciprocal of the other line's slope. So in this case, the slope would be 1, since the negative reciprocal of -1 is 1/1 which is 1.
To find the y-intercept, you have to substitute the point (8,2) into y = mx + b
2 = 1(8) + b
b = -6
The equation is y = x - 6
The equation of the line which is perpendicular and goes through the point (8,2) is y = x - 6
The equation of the required line in slope-intercept form is expressed as:
y-y0 = m(x-x0) where:
m is the slope(x0, y0) is the point on the lineGiven the equation of the line as y = -x
Get the slope of the line
mx = -x
m = -1
Since the required line is perpendicular to this line, the required slope will be 1 (M = -(-1/1))
Get the required equation
Recall that;
y-y0 = m(x-x0)
y - 2 = 1(x-8)
y - 2 = x - 8
y = x - 8 + 2
y = x - 6
Hence the equation of the line which is perpendicular and goes through the point (8,2) is y = x - 6.
Learn more here: https://brainly.com/question/17003809
Please help it would be apreacated
What is the name of the line of reflection for the pair of figures?
Enter your answer in the box.
Line ___
Hi!
Answer - Line R
Well refraction is the bending of something. I choose r because it may have refraction because of the 2 rectangles at the end of both sides.
Hope This Helps!
△ABC is mapped to △A′B′C′ using the rule (x, y)→(−x, −y) followed by (x, y)→(x, −y) .
Which statement correctly describes the relationship between △ABC and △A′B′C′ ?
A. △ABC is congruent to △A′B′C′ because the rules represent a reflection followed by a rotation, which is a sequence of rigid motions.
B. △ABC is congruent to △A′B′C′ because the rules represent a rotation followed by a reflection, which is a sequence of rigid motions.
C. △ABC is not congruent to △A′B′C′ because the rules do not represent a sequence of rigid motions.
D. △ABC is congruent to △A′B′C′ because the rules represent a reflection followed by a reflection, which is a sequence of rigid motions.
Answer:
B. △ABC is congruent to △A′B′C′ because the rules represent a rotation followed by a reflection, which is a sequence of rigid motions.
Step-by-step explanation:
I just took the test, good luck! Have a wonderful day! :)
Transformation involves changing the position of a shape.
The correct statement is: (b) △ABC is congruent to △A′B′C′ because the rules represent a rotation followed by a reflection, which is a sequence of rigid motions.
The transformation rule is given as:
[tex]\mathbf{(x,y) \to (-x,-y)}[/tex], then:
[tex]\mathbf{(x,y) \to (x,-y)}[/tex]
The first transformation [tex]\mathbf{(x,y) \to (-x,-y)}[/tex] is 180 degrees rotation across the originThe second transformation [tex]\mathbf{(x,y) \to (x,-y)}[/tex] is a reflection across the x-axisRotation and reflection are both rigid transformation.
Hence, the correct option is (b):
Read more about rotation and reflection at:
https://brainly.com/question/15577335
What is the equation of the following graph in vertex form?
Courtesy of Texas Instruments (2 points)
y = (x - 3)2 - 1
y = (x + 3)2 - 1
y = (x - 4)2 - 2
y = (x - 4)2 + 8
For this case we have:
The equation in vertex form of the parabola is given by:
[tex]y = a (x-h) ^ 2 + k\\[/tex]
The vertex is (h, k) and is given by the highest or lowest point of the parabola, in this case it is observed that it is [tex](h, k) = (- 3, -1)\\[/tex]
Thus, the equation is given by:
[tex]y = a (x - (- 3)) ^ 2 + (- 1)\\\\y = a (x + 3) ^ 2-1\\[/tex]
We look for the value of a, substituting a point of the parabola in the equation in the form of vertex, we will take the point [tex](x, y) = (0,8)\\[/tex]
Substituting we have:
[tex]8 = a (0 - (- 3)) ^ 2 + (- 1)\\\\8 = a (0 + 3) ^ 2-1\\\\8 = a (3) ^ 2-1\\[/tex]
[tex]8 = 9a-1\\\\8 + 1 = 9a\\\\9 = 9a\\[/tex]
[tex]a = \frac{9}{9}\\\\a = 1\\[/tex]
Thus, the equation of the parabola is given by:
[tex]y = (x + 3) ^ 2-1\\[/tex]
Answer:
[tex]y = (x + 3) ^ 2-1[/tex]
Answer:
y = (x + 3)2 - 1
Step-by-step explanation:
Find the system determinant of the given matrix. [2, 4] [3,-9]
[tex]\left[\begin{array}{ccc}2&4\\3&-9\end{array}\right]\\\\\det\left[\begin{array}{ccc}2&4\\3&-9\end{array}\right]=(2)(-9)-(4)(3)=-18-12=-30[/tex]
Answer:
-30 will be the determinant.
Step-by-step explanation:
We have to find the system determinant of the given matrix
[tex]\begin{bmatrix}2 & 4\\ 3 & -9\end{bmatrix}[/tex]
Determinant will be = 2(-9) - (4 × 3)
= -18 -12
= -30
Therefore, as per given options by you in the comments.
option A is the answer.
Which of the following equations correctly describes the graphed line?
y = 2/3x - 2
y = -2/3x - 2
y = 2/3x + 2
y = -2/3x + 2
y = - [tex]\frac{2}{3}[/tex] x - 2
the equation of a line in ' slope - intercept form ' is
y = mx + c ( m is the slope and c the y- intercept ) calculate m using the gradient formula
m = (y₂ - y₁ ) / (x₂ - x₁ )
with (x₁, y₁ ) = (0 , - 2 ) and (x₂ , y₂ ) = A( 6 , - 6 )
m = [tex]\frac{- 6+ 2}{6 - 0}[/tex] = [tex]\frac{-4}{6}[/tex] = - [tex]\frac{2}{3}[/tex]
y -intercept c = - 2 ( from graph )
y = - [tex]\frac{2}{3}[/tex] x - 2
For y = 3x - 2x2 +5x3, show how to find the value for y, when x = 3. Show your work
Answer:
y= 126
Step-by-step explanation:
The given equation is: y= 3x-2x^2+5x^3
Substituting the value x=3 in the above equation,we get
y= 3(3)-2(3)^2+5(3)^3
⇒y= 9-2(9)+5(27)
⇒y= 9-18+135
⇒y= 126
What graph represents the inequality y≥2−2x?
[tex]y\geq2-2x\\\\\text{Let's the line}\ y=2-2x\\\\for\ x=0\to y=2-2(0)=2\to(0,\ 2)\\for\ x=1\to y=2-2(1)=0\to(1,\ 0)[/tex]
[tex]\text{draw a line and shade above the line}\\\\\text{Look at the picture}[/tex]
Answer:
Graph is attached below
Step-by-step explanation:
To graph the given inequality , replace the inequality sign by = sign
y≥2−2x
y=2−2x
Now make a table , assume some random number for x and find out y
x y=2-2x
0 2
1 0
2 -2
Now graph all the points (0,2) (1,0) (2,-2)
Now we do shading. For shading use test point (0,0)
plug in 0 for x and 0 for y
[tex]y\geq 2-2x[/tex]
[tex]0\geq 2-2(0)[/tex]
[tex]0\geq 2[/tex] is false
So shade the region that does not contain (0,0)
The graph is attached below
25 Points! Pre-Calc help? Will award brainliest.
Find the solution set of the given equation for 0 ≤ x ≤ 2π.
-tanA = -1
A. pi/4, 3pi/4
B. pi4/, 5pi/4
C. 3pi/4, 5pi/4
D. 3pi/4, 7pi/4
The answer is B. If you look at a graph of -tan (which is cot), the places the graph crosses -1 are at pi/4 plus kpi. If you add pi to pi/4, you get 5pi/4, and these two answers are in B only.
Im adding an answer so the other guy that gave an answer gets his points.
A toy jeep is 12 1/2 inches long while an actual Jeep measures 18 3/4 ft long what is the value of the ratio length of a toy Jeep to the length of a actual Jeep
The length of toy jeep = [tex]12 \frac{1}{2}[/tex]
= [tex]\frac{25}{2}[/tex] inches
The length of actual Jeep = [tex]18 \frac{3}{4}[/tex] feet
We have to find the ratio length of a toy jeep to the length of actual jeep.
Firstly, we will make the dimensions of the both the given lengths same.
As 1 foot = 12 inches
[tex]18 \frac{3}{4}[/tex] feet = [tex]18 \frac{3}{4} \times 12[/tex] inches
=[tex]\frac{75 \times 12}{4}[/tex]
= 225 inches
So, the ratio length of toy jeep to actual jeep
= [tex]\frac{25}{2} \div 225[/tex]
= [tex]\frac{25}{2} \times \frac{1}{225}[/tex]
= [tex]\frac{1}{18}[/tex]
= 1:18
So, the ratio length of a toy Jeep to the length of a actual Jeep is 1:18.
Length of toy jeep = [tex]12\frac{1}{2}=\frac{25}{2}[/tex] inches
Length of actual jeep = [tex]18\frac{3}{4}=\frac{75}{4}[/tex] feet
Now to find the ratio between the two, we must convert both of them in same units. So, lets convert the actual jeep length in feet to inches.
1 feet = 12 inches.
So, [tex]\frac{75}{4}[/tex] feet = [tex]\frac{75}{4}\times12=225[/tex] inches
Ratio of length of toy jeep to actual jeep will be =
[tex]\frac{\frac{25}{2}}{225}[/tex]
[tex]\frac{25}{2\times225}[/tex]
[tex]\frac{25}{450}[/tex] = [tex]\frac{5}{90}[/tex]
ratio is : [tex]\frac{1}{18}[/tex] or 1:18
Which of the following numbers is divisible by 3 and 9?
A. 74,028
B. 40,653
C. 62,997
D. 95,376
The number that is divisible by 3 and 9 is 40,653.
What is division?The division is the process of sharing a collection of items into equal parts and is one of the basic arithmetic operations in maths.
We may face different situations every day where we use the division technique.
Given are numbers, we need to find which of them numbers are divisible by 3 and 9,
LCM of 3 and 9 is 9,
So numbers completely divisible by 9 will also be divisible by 3.
The only number from the option which is completely divisible by 9 is 40,653.
Hence, the number that is divisible by 3 and 9 is 40,653.
Learn more about division, click;
https://brainly.com/question/21416852
#SPJ2
What is the perimeter of the triangle shown on the coordinate plane, to the nearest tenth of a unit? A.24.8 units B.27.8 units C.28.5 units D.30.9 units
The answer is B I hope I helped
Answer:
the answer is B.28.7 hope i helped you learn something new
Step-by-step explanatio
IF WORK IS SHOWN YOU'LL BE MARKED BRAINLIEST
row #of students
1 4
2 7
3 10
4 13
Which formula can be used to find the number of students seated in any given row?
a. an= 4n
b. an= 4n – 1
c. an= n + 3
d. an= 3n + 1
I believe its asking you the formula to find the rows numbers moving forward
Examle row 5 will be 16, I believe that is B. 4n - 1
solve.
14n + 6p - 8n = 18p for n
[tex]14n+6p-8n=18p\ \ \ \ |\text{subtract 6p from both sides}\\\\14n-8n=12p\\\\6n=12p\ \ \ \ |\text{divide both sides by 6}\\\\\boxed{n=2p}[/tex]
The correct solution for this equation is n = 2p.
I hope this helped! :)
A jet ski depreciates at 11% of its original value each year. If the jet ski was $8,000 as it’s time of purchase, what is the value of the jet ski after 5 years
f(x) = 8000 - (8000)(0.11)x
= 8000 - 880x
f(5) = 8000 - 880(5)
= 8000 - 4400
= 3600
Answer: $3,600
Answer:
$4467.25
Step-by-step explanation:
We have been given that a jet ski depreciates at 11% of its original value each year. The jet ski was $8,000 as it’s time of purchase.
We will exponential decay function to solve our given problem.
[tex]y=a\cdot(1-r)^x[/tex], where,
a = Initial value,
r = Decay rate in decimal form.
[tex]r=\frac{11}{100}=0.11[/tex]
[tex]y=\$8,000\cdot(1-0.11)^5[/tex]
[tex]y=\$8,000\cdot(0.89)^5[/tex]
[tex]y=\$8,000\cdot 0.5584059449[/tex]
[tex]y=\$4467.2475592[/tex]
[tex]y\approx \$4467.25[/tex]
Therefore, the value of ski jet after 5 years would be $4467.25.
Explain why a vertical line is said to have undefined slope or no slope.
Cristoble used synthetic division to divide the polynomial f(x) by x + 3, as shown on the table. What is the value of f(−3) ? −3 2 33 36 A synthetic division setup with respective columns containing the following numbers column 1 containing -3 as the divisor, column 2 containing 2, blank and 2, column 3 containing negative 5, negative 6, negative 11, and column 4 containing 3, 33, 36.There is a line above the numbers 2, negative 11 and 36.
Answer:
Remainder is 36.
Step-by-step explanation:
We are given that f(x) is divided by x+3 using synthetic division, and we are given with table attached in the image.
In synthetic division, first row represents the coefficients of dividend. From the given table, dividend is f(x)=[tex]2x^{2}-5x+3[/tex] and since f(x) is divided by x+3, divisor is -3.
First two numbers of last row represents coefficients of quotient and last most number of third row is remainder.
And we can write f(x) as (x+3)(2x-11)+36.
Hence remainder is 36 , when f(x) is divided by x+3.
Answer:
36
Step-by-step explanation:
this i believe is the settup u were describing
A cement bridge post is 24 inches square and 15 feet 9 inches in length. If the cement weighs 145 pounds per cubic foot, how much does one bridge post weigh? A. 9,280 pounds B. 9,222 pounds C. 9,135 pounds D. 8,700 pounds
Answer:
The answer is option (C), One cement bridge post weighs 9,135 pounds
Step-by-step explanation:
Step 1: Get the total volume of a cement bridge post
The cement bridge post is in the shape of a cuboid, therefor the volume of the cement bridge post can be expressed as;
Volume of cement bridge post=Base area×Length
where;
Base area=(24^2) inches square
1 foot=12 inches
Convert 24 inches to foot=24/12=2^2=4 feet²
Length=15 feet and 9 inches
1 foot=12 inches
Convert 9 inches to foot=9/12=0.75 feet
Total length=(15+0.75)=15.75 feet
replacing;
Volume of cement bridge post=(4×15.75)=63 cubic feet
Volume of cement bridge post=63 cubic feet
Step 2: Get the total weight of the cement bridge post
Total weight of the cement bridge post=Weight per cubic foot×total volume of the cement bridge post
where;
Weight per cubic foot=145 pounds per cubic foot
Total volume of the cement bridge post=63 cubic feet
replacing;
Total weight of the cement bridge post=(145×63)=9,135 pounds
One cement bridge post weighs 9,135 pounds